Financial Management Training for Micro Business to Maintain Existence in The Digital Era - Oktafia, Renny; Muhammad Ilham Naufal (PT Inovasi Pratama Internasional, 2023)
Village Owned Enterprises is a business entity established with the aim of helping provide facilities to local village communities to be able to develop entrepreneurial skills, starting from creativity to produce an item that can generate selling value and use value over a long period of time, by In other words, they are able to compete in terms of quality. However, it is very unfortunate when the active members of Village Owned Enterprises do not yet have the skills to keep financial records which is one of the important aspects of running a business. This activity aims to provide training to every active member of the Village Owned Enterprise in the Kludan Village, Sidoarjo with the Asset Based Communities Development method with several stages that have been carried out including conducting studies, having dreams or targets, setting procedures, setting clear goals and having self-determination. It is hoped that the service activities that have been carried out will have a positive impact by demonstrating the development of the abilities possessed by each member of the Village Owned Enterprise in utilizing financial literacy.